The container port of Buenos Aires in the mega-ship era - Olaf Merk (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2018)
Can the container port of Buenos Aires be adapted to the demands of the mega-ship era? Ever-larger ships and the cargo peaks they cause imply new requirements for container ports. This paper examines strategies for Argentina's largest port, whose three container terminal concessions will expire in 2020.
Keywords: 330